Bemerkungen zu einer Rezension, und zugleich Überlegungen zur Editionspraxis christlich-arabischer bzw. äthiopischer Übersetzungsliteratur - Heide, Martin (Aethiopica, 2017)
A recently published review on the Testament of Abraham (as ed. by M. Heide) is raising important questions that deal with the adequate method of preparing critical editions of Oriental texts. Besides, the review has not a small number of misunderstandings that need to be clarified.